TransMilenio: experience, crowd and non-place - Durán Segura, Luis Armando (2017)
The massive transport systems in Latin America have significantly transformed economic planning, territorial planning, urban design and, in particular, the experiences of the people who use them on a daily basis. This text explores, using ethnographic elements, the case of the TransMilenio in Bogotá, as a non-place and as a crowd. Field notes are used, made during the years 2011, 2012 and 2016, to portray some relevant characteristics of contemporary urban life.